Frequently asked questions about in vivo chlorophyll fluorescence: practical issues - Kalaji, Hazem (2014)
The aim of this educational review is to providepractical information on the hardware, methodology, andthe hands on application of chlorophyll (Chl)afluores-cence technology. We present the paper in a question andanswer format like frequently asked questions. Althoughnearly all information on the application of Chlafluores-cence can be found in the literature, it is not always easilyaccessible. This paper is primarily aimed at scientists whohave some experience with the application of Chlafluo-rescence but are still in the process of discovering what itall means and how it can be used. Topics discussed are(among other things) the kind of information that can beobtained using different fluorescence techniques, theinterpretation of Chlafluorescence signals, specificapplications of these techniques, and practical advice ondifferent subjects, such as on the length of dark adaptationbefore measurement of the Chlafluorescence transient.